Fe sources and transport from the Antarctic Peninsula shelf to the southern Scotia Sea. (August 2019) - Jiang, Mingshun; Measures, Christopher I.; Barbeau, Katherine A.; Charette, Matthew A.; Gille, Sarah T.; Hatta, Mariko; Kahru, Mati; Mitchell, B. Gregory; Naveira Garabato, Alberto C.; Reiss, Christian; Selph, Karen; Zhou, Meng
Abstract: The Antarctic Peninsula (AP) shelf is an important source of dissolved iron (Fe) to the upper ocean in the southern Scotia Sea, one of the most productive regions of the Southern Ocean. Here we present results from a four-year (2003-2006) numerical simulation using a regional coupled physical-biogeochemical model to assess the Fe sources and transport on the AP shelf and toward the southern Scotia Sea. The model was validated with a suite of data derived from in situ surveys and remote sensing. Model results indicate that sediments in the AP shelf and the South Orkney Plateau (SOP) provide the dominant source of Fe to the upper 500 m in the southern Scotia Sea. Additional Fe inputs to the region are associated with the Antarctic Circumpolar Current (ACC) and the northern limb of the Weddell Gyre, deep-ocean sediment sources, dust deposition, and icebergs. Fe on the AP shelf originates primarily from sediments on the relatively shallow inner shelf and is directly injected into the water column and subsequently transported toward Elephant Island by the confluent shelf currents. Off-shelf Fe export is primarily through entrainment of shelf waters by the ACC's Southern Boundary frontal jet along the northern edge of the AP shelf, the Hesperides Trough, and the SOP shelf. About 70% of the off-shelf export takes place below the surface mixed layer, and is subsequently re-supplied to the euphotic zone through vertical mixing, mainly during austral fall and winter. The exported shelf-derived Fe is then advected downstream by the ACC and Weddell Gyre and spread over the southern and eastern Scotia Seas. Taken together, shelf Fe export witin top 500 m meets nearly all of the Fe demand of phytoplankton photosynthesis in the southern Scotia Sea. Waters with elevated Fe concentrations in the Scotia Sea are largely restricted to south of the Southern ACC Front. Highlights: Shelf Fe transport has complex pathways through shelf currents and ACC. Shelf-derived Fe is the dominant Fe source to the southern Scotia Sea. Shelf Fe originates mainly from inner shelf of the western Antarctic Peninsula. Shelf-derived Fe meets phytoplankton Fe demand in the southern Scotia Sea.